Impact of Coronary Calcification on Clinical Management in Patients With Acute Chest Pain. (May 2017) - Bittner, Daniel O.; Mayrhofer, Thomas; Bamberg, Fabian; Hallett, Travis R.; Janjua, Sumbal; Addison, Daniel; Nagurney, John T.; Udelson, James E.; Lu, Michael T.; Truong, Quynh A.; Woodard, Pamela K.; Hollander, Judd E.; et al.
Abstract : Background—: Coronary artery calcification (CAC) may impair diagnostic assessment of coronary computed tomography angiography (CTA). We determined whether CAC affects efficiency of coronary CTA in patients with suspected acute coronary syndrome (ACS). Methods and Results—: This is a pooled analysis of ACRIN-PA (American College of Radiology Imaging Network–Pennsylvania) 4005 and the ROMICAT-II trial (Rule Out Myocardial Infarction/Ischemia Using Computer Assisted Tomography) comparing an initial coronary CTA strategy to standard of care in acute chest pain patients. In the CTA arms, we investigated appropriateness of downstream testing, cost, and diagnostic yield to identify patients with obstructive coronary artery disease on subsequent invasive coronary angiography across CAC score strata (Agatston score: 0, >0–10, >10–100, >100–400, >400). Out of 1234 patients (mean age 51±8.8 years), 80 (6.5%) had obstructive coronary artery disease (≥70% stenosis) and 68 (5.5%) had ACS. Prevalence of obstructive coronary artery disease (1%–64%), ACS (1%–44%), downstream testing (4%–72%), and total (2337–8484 US$) and diagnostic cost (2310–6678 US$) increased across CAC strata ( P <0.001). As the increase in testing and cost were lower than the increase of ACS rate in patients with CAC>400, cost to diagnose one ACS was lowest in this group (19 283 US$ versus 464 399 US$) as compared with patients without CAC. The diagnostic yield of invasive coronary angiography was highest in patients with CAC>400 (87% versus 38%). Conclusions—: Downstream testing, total, and diagnostic cost increased with increasing CAC, but were found to be appropriate because obstructive coronary artery disease and ACS were more prevalent in patients with high CAC. In patients with acute chest pain undergoing coronary CTA, cost-efficient testing and excellent diagnostic yield can be achieved even with high CAC burden. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifiers: NCT01084239 and NCT00933400. Abstract : Supplemental Digital Content is available in the text.